Hubungan Waktu Tunggu dan Jenis Jaminan Kesehatan terhadap Tingkat Kepuasan Pasien Rawat Jalan di Rumah Sakit Lampung Eye Center - Rukmono, Prambudi; Yuliaty, Farida; Rulia, Rulia (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of waiting time and type of health insurance on patient satisfaction. Using a quantitative approach, research was conducted on outpatients at the Lampung Eye Center Hospital in Bandar Lampung, with a population of 7,998 people and a sample of 382 patients selected randomly. The independent variables in this study are waiting time and type of health insurance, while the dependent variable is patient satisfaction. Data was collected using a questionnaire and analyzed using multiple linear regression. The t test results show that waiting time (P Value = 0.000) and type of health insurance (P Value = 0.015) each have a significant effect on patient satisfaction. The F test also confirmed that these two variables jointly influence patient satisfaction (P Value = 0.000). Overall, both waiting time and type of health insurance have a significant effect on the level of patient satisfaction, both partially and simultaneously.